A Novel Regimen for Treating Melanoma: MCL1 Inhibitors and Azacitidine - Chiara R. Dart; Nabanita Mukherjee; Carol M. Amato; Anabel Goulding; Morgan MacBeth; Robert Van Gulick; Kasey L. Couts; James R. Lambert; David A. Norris; William A. Robinson; Yiqun G. Shellman (MDPI AG, 2021)
Although treatment options for melanoma patients have expanded in recent years with the approval of immunotherapy and targeted therapy, there is still an unmet need for new treatment options for patients that are ineligible for, or resistant to these therapies. BH3 mimetics, drugs that mimic the activity of pro-apoptotic BCL2 family proteins, have recently achieved remarkable success in the clinical setting. The combination of BH3 mimetic ABT-199 (venetoclax) plus azacitidine has shown substantial benefit in treating acute myelogenous leukemia. We evaluated the efficacy of various combinations of BH3 mimetic + azacitidine in fourteen human melanoma cell lines from cutaneous, mucosal, acral and uveal subtypes. Using a combination of cell viability assay, BCL2 family knockdown cell lines, live cell imaging, and sphere formation assay, we found that combining inhibition of MCL1, an anti-apoptotic BCL2 protein, with azacitidine had substantial pro-apoptotic effects in multiple melanoma cell lines. Specifically, this combination reduced cell viability, proliferation, sphere formation, and induced apoptosis. In addition, this combination is highly effective at reducing cell viability in rare mucosal and uveal subtypes. Overall, our data suggest this combination as a promising therapeutic option for some patients with melanoma and should be further explored in clinical trials.